A Case of Heart Failure in a Patient With Systemic Lupus Erythematosus - Heriberto Matos Santana, MD; Brittain Heindl, MD; Sarabjeet Suri, MD; Salma Khatoon, MD; Sudeep Aryal, MD; Arka Chatterjee, MD; Silvio Litovsky, MD; Hamdy Ahmed, MD; Amanda Schnell, MD; Indranee Rajapreyar, MD (JACC: Case Reports, 2020)
Patients with systemic lupus erythematosus (SLE) can present with multiple cardiovascular pathologies, including pulmonary hypertension, valvular disease, pericarditis, myocarditis, and premature atherosclerosis. SLE medications can also cause cardiovascular side effects. We present a patient who developed a severe cardiomyopathy secondary to the hydroxychloroquine prescribed to treat her SLE. (Level of Difficulty: Beginner.)